Jenis dan Status Konservasi Ikan Hiu yang Tertangkap di Tempat Pelelangan Ikan (TPI) Labuan Bajo, Manggarai Barat, Flores - Ismail Syakurachman Alaydrus; Narti Fitriana; Yohannes Jamu (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2014)
The study aimed to determine the types of sharks are caught, sold and conservation status in the fish auction place (TPI) Labuan Bajo, West Manggarai, Flores, East Nusa Tenggara have been conducted in February and March 2014 in Labuan Bajo. The research method was the survey method and used Market Survey sampling techniques and identification by Rapid Assessment method. Descriptively analyzed data, displayed in the form of narration and a table. Based on the results of the study, found 114 individual sharks, 55 individual males, 59 females were classified into three orders, namely Orectolobiformes, Lamniformes, and Carcharhiniformes; 4 families that Carcharhinidae, Odontaspididae, Rhynchobatidae, and Ginglymostomatidae; 5 genera namely Carcharhinus, Triaenodon, Rhyncobatus, Prionace, and Rhizoprionodon and 9 types of sharks that Carcharhinus melanopterus, Triaenodon obesus, Carcharhinus limbatus, Carcharhinus taurus, Carcharhinus amblyrhynchos, Rhynchobatus australiae, Prionace glauca, Rhizoprionodon acutus, and Nebrius ferrugineus. Based on the state of conservation, shark found in Labuan Bajo TPI classified Vulnerable and Near Threatened, the dominant type of shark found is Carcharhinus melanopterus (91 fishes) while the least was found is Rhynchobatus australiae, Prionace glauca, Rhizoprionodon acutus, and Nebrius ferrugineus (each 1 individual).